Malay Muslim integration in upper southern provinces: Role of the Thai government - Md Mahbubul, Haque (2019)
Migration by nature can lead to integration. This is possible when a nation-state takes a clear stand on the practices of multiculturalism. Most Asian countries have failed to adopt multiculturalism and rather practice the policy of assimilation. Yet multiculturalism has become popular as this concept incorporates recognition of ethnic and national minorities and supports their cultural identity. Due to longstanding conflict in the southernmost provinces of Thailand, various data suggests that many Malay-Muslims migrated to the upper southern provinces of Thailand in recent years. In this context, internal migration occurred mainly for economic as well as security reasons. Consequently, in some provinces demographic numbers have changed. In the near future, there may be changes in Thai society, especially in the upper southern provinces. The main purpose of this study is to ascertain how the government accommodates internal migration especially in upper southern provinces. In order to develop a multicultural society, the Thai government should nurture minority issues in various ways. Apart from the government, Thai civil society—comprising academics and NGOS—has addressed it from their own perspectives. Still, there is no comprehensive approach to deal with this issue. Aside from the lack of cultural and political integration, Thai society may face severe related challenges to migration in the next decade.